Biological and Physiological Markers of Tactile Sensorial Processing in Healthy Newborns - Gonçalves, MG (2016)
The main objective of this review is to provide a descriptive analysis of the biological and physiological markers of tactile sensorial processing in healthy, full-term newborns. Research articles were selected according to the following study design criteria: (a) tactile stimulation for touch sense as an independent variable; (b) having at least one biological or physiological variable as a dependent variable; and (c) the group of participants were characterized as full-term and healthy newborns; a mixed group of full-term newborns and preterm newborns; or premature newborns with appropriate-weight-for-gestational age and without clinical differences or considered to have a normal, healthy somatosensory system. Studies were then grouped according to the dependent variable type, and only those that met the aforementioned three major criteria were described. Cortisol level, growth measures, and urinary catecholamine, serotonin, and melatonin levels were reported as biological-marker candidates for tactile sensorial processing. Heart rate, body temperature, skin-conductance activity, and vagal reactivity were described as neurovegetative-marker candidates. Somatosensory evoked potentials, somatosensory evoked magnetic fields, and functional neuroimaging data also were included.